Tinjauan Yuridis Perlindungan Konsumen pada Transaksi E-Commerce Menurut Undang-Undang Perlindungan Konsumen - Insania Khairunnisa; Vina Agustina; Fachriana Fachriana; Susantonius Selamat Hia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
The acceleration of digital transformation in the national trade sector has led to a significant surge in e-commerce activity across Indonesia, opening up market access that transcends geographical and temporal limitations. Nevertheless, behind this transactional convenience, the digital commerce ecosystem harbors a number of potential risks for consumers, including inaccurate product information, delivery failures, online fraud schemes, and the illegal exploitation of personal data. Structurally, consumers occupy an asymmetrical position relative to businesses in digital trade relationships, a dynamic exacerbated by information asymmetry, limited bargaining power, and low legal literacy. This study focuses on a legal analysis of the consumer protection framework within the e-commerce ecosystem, systematically referencing Law No. 8 of 1999 on Consumer Protection along with its derivative and complementary regulations in the digital era. The research was conducted using a normative legal approach reinforced by conceptual analysis, utilizing secondary legal materials that include primary, secondary, and tertiary sources. The results of the study indicate that although Indonesia’s normative framework for digital consumer protection is formally in place, its implementation in e-commerce practice still reveals substantial gaps. Based on this, this study recommends structured regulatory harmonization, strengthening the institutional capacity of regulatory bodies, expanding digital legal literacy among the public, and establishing platform accountability mechanisms as prerequisites for achieving genuine consumer protection in the realm of e-commerce.